Burnout syndrome among general practitioners in the Czech Republic: a repeated survey study - Štěpánek, Ladislav; Horáková, Dagmar; Král, Norbert; Štěpánek, Lubomír; Býma, Svatopluk (BMC primary care, 2024)
BACKGROUND: Given the critical role of general practitioners (GPs), their insufficient medical density and the adverse effects of burnout on both practitioners and the quality of care provided, the prevalence estimates of GP burnout reported in the literature are highly concerning. This nationwide study builds on a 2023 survey that revealed a significant burden of burnout among Czech GPs. The primary objectives were to analyse the prevalence and determinants of burnout and to examine potential trends over time. METHODS: In April 2024, 2,500 randomly selected GPs were emailed the Maslach Burnout Inventory - Human Services Survey for Medical Personnel, supplemented with sociodemographic and job-related questions. The statistical analysis included a comparison with an identical study conducted a year earlier. RESULTS: Of the 765 completed responses (542 females, 223 males; mean age 55.5 years), 19.7% of the GPs experienced burnout in all three dimensions, 23% in two, 28.5% in one, and 28.8% in no dimension. Similar to 2023, the most common burnout dimension was a lack of personal accomplishment (PA, 52.2%), followed by emotional exhaustion (EE, 45.9%) and depersonalization (DP, 35.7%). Male and employed GPs experienced greater degrees of DP, while practice owners were more susceptible to EE. A positive dependence of burnout on the number of listed patients was identified. The proportion of GPs experiencing burnout across all dimensions decreased by 2.1% from 2023 to 2024 (p = 0.232), primarily in DP. Additionally, a 6.7% increase in GPs showing no signs of burnout in all dimensions (p = 0.002) further supported this positive trend. CONCLUSIONS: Between 2023 and 2024, the prevalence of burnout among GPs exhibited a modest decline. Nonetheless, it persists at almost 20%. Ensuring a sufficiently dense network of GPs, providing adequate resource allocation, and raising awareness of their importance are essential measures.
Keywords: Česká republika; lidé středního věku; Depersonalization; depersonalizace; profesionální vyhoření; lidé; Adult; praktičtí lékaři; Middle Aged; Czech Republic; dospělí; průzkumy a dotazníky; Burnout, Professional; Female; pracovní uspokojení; Male; Surveys and Questionnaires; ženské pohlaví; Humans; mužské pohlaví; prevalence; Job Satisfaction; General Practitioners; Prevalence